Treatment Outcome of Posteromedial Procedure for Neglected Clubfoot in Children Older than 2 Years of Age - Report of 3 Cases - Iman Dwi Winanto (PT Kalbe Farma Tbk., 2021)
Background: A neglected clubfoot is a clubfoot that didn’t get early or adequate treatment; it is a significant problem in developing countries. The posteromedial soft tissue release procedure is one of the surgical techniques in clubfoot treatment. Case: Three patients with neglected clubfoot were assessed before and after treatment. All patients were treated with posteromedial soft tissue release method followed by serial application of above-knee plaster of parts for three months. Result: Two cases had a good correction, one case had a fair correction. Conclusion: The posteromedial soft tissue release with proper follow up and splinting results in a cosmetically normal appearance and functionally acceptable pain-free foot in neglected clubfoot in children older than two years of age. Latar Belakang: Neglected clubfoot merupakan clubfoot yang tidak ditatalaksana atau mendapat tata laksana awal tidak adekuat; kondisi ini sering ditemui di negara berkembang. Prosedur posteromedial soft tissue release merupakan salah satu teknik operasi dalam tatala ksana clubfoot. Kasus: Tiga pasien neglected clubfoot ditatalaksana dengan prosedur posteromedial soft tissue release diikuti aplikasi serial plaster of paris di atas lutut selama tiga bulan. Hasil: Dua kasus menunjukkan hasil koreksi baik dan 1 kasus hasil koreksi sedang. Simpulan: Prosedur posteromedial soft tissue release dikombinasi dengan ¬follow up serta teknik splinting yang adekuat memberikan hasil kosmetik yang baik serta kaki bebas nyeri pada kasus neglected clubfoot anak berusia di atas dua tahun